Association Between Clinical Manifestations of Covid-19 Patients Post Immunization Follow-Up (Aefi) With Cardiovascular Commorbidities and It’s Islamic Perspective Review - Hasyajogi Tiara Harahap; Lilian Batubara; Endy Muhammad Istiwara (Junior Medical Journal, 2023)
Introduction : the use of the COVID-19 vaccine can occur AEFIs which are adverse medical events and occur after immunization, but these events are not always related to the use of the vaccine. Adverse Post-Immunization Events (AEFIs) can be in the form of vaccine reactions, coincidental events, anxiety reactions, and causal relationships that cannot be determined. Post-Immunization Follow-Up Events (KIPI) COVID-19 has a different reaction, duration, symptoms and severity for everyone and not everyone experiences Post-Immunization Adjunct Events (KIPI). This study aims to determine the relationship between clinical manifestations of Post-Immunization Adverse Events (AEFI) in COVID-19 patients with cardiovascular comorbidities.Method : This research was a descriptive observational study using a cross-sectional method. The sample in this study were 54 respondents who were COVID-19 patients at the Palmerah District Health Center who had been vaccinated 3 months after recovering from COVID-19. Data was collected by conducting direct interviews with respondents. Bivariate analysis was performed using the Chi-Square statistical test with Fisher Exact Test analysis.Result : From the results of the analysis conducted, there were 49 respondents (90.7%) who had cardiovascular comorbidities with 45 respondents (93.8%) of whom had Post-Immunization Adjunct Events (KIPI) and 4 respondents (8.2%) who did not experience Post-Immunization Adjunct Events (KIPI). The results of the Chi-Square test with the Fisher Exact Test Analysis obtained a significance value of 0.089. Therefore, the value of Sig. (2-sided) is 0.089 (0.05), which means that there is no association between cardiovascular comorbidities and Post-Immunization Adverse Events (AEFI).Conclusion : There is no significant association between cardiovascular comorbidities and Post Immunization Adverse Events (AEFI).